APPLICATION OF LEARNING USING THE CHAIN GAME METHOD FOR CHILDREN WITH SPECIAL NEEDS (MENTALLY RETARTED) AT PEKALONGAN STATE SLB - Salsabila, Marshanda Salsabila (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
One of the community service activities is through the socialization of the Implementation of Learning Using the Chain Game Method for Children with Special Needs (Tuna Ghraita) at the Pekalongan State SLB, we are very enthusiastic. students, totaling 4 people with provisions from the campus, alhamdulillah, socializing smoothly and full of joy. The socialization of physical fitness education was carried out on Friday, June 9 2023 at 09.00, the place in the Pekalongan State SLB classroom. In the student team, which consisted of 4 people, each of them had their respective duties as presenters about the order of providing heating and cooling, there was a section that arranged student lines and there was also a photo documenter. In this activity students see and practice carefully how the presenter gives educational material on the Application of Learning Using the Chain Game Method. From this we can conclude that there is very good and conducive communication from the presenters and students which students can understand. Keywords: Chain game, Learning